Efeitos da configuração urbana na acidentalidade envolvendo pedestres em cidades de porte médio - Carmo, Cássio Leandro do (2013)
This work aims to analyze the urban pedestrian crashes and their correlation with the urban form in the cities of São Carlos and São José do Rio Preto. Accidents are characterized, through graphs and tables, according to the occurrence at intersections or along the streets, vehicles involved and severity of injury, day of week, time, gender and age of victims. Accidents georeferencing is done through Geographic Information System, using the software TransCAD. The urban road configuration of the cities and the correlation with the accidents are verified through the Theory of Space Syntax, determining their properties with Depthmap, a spatial analysis software. Although these cities present good levels of social development, they reflect the poor national performance in terms of road safety of pedestrians. The data evince that in recent years the number of pedestrian-crashes has at least stabilized, despite the large increase of the vehicle fleet. Regarding the configuration of the structure of urban road network and the location of accidents, the analysis according to the Space Syntax indicates that most accidents occur on roads which are more connected, with more global or local integration, and occupied by commercial or service activities. However, there are not necessarily accidents in streets or avenues with significant syntactic indexes, which demonstrates a restriction of analysis using solely the Syntax. Verification of correlation with the urban form through the Theory of Space Syntax suggests that local integration is a good parameter approach, especially in the initial planning of road safety, but still dependent on other essential variables of Traffic Engineering and Urban Planning, such as geometric characteristics of the road and land use.